A Review of Propylene Glycol-free Melphalan Conditioning for Hematopoietic Cell Transplantation for Multiple Myeloma and Light Chain Amyloidosis - Hari, Parameswaran; Chhabra, Saurabh (Transplantation and cellular therapy, 2022)
Autologous hematopoietic cell transplantation (AHCT) remains a standard therapeutic option for patients with multiple myeloma (MM). Outcomes have improved for this patient group after first AHCT, with the use of novel agents in induction, as well as post-transplantation maintenance. High-dose melphalan remains the gold standard as the conditioning regimen for MM. Traditional melphalan is a lyophilized formulation that after reconstitution has insufficient chemical stability and water solubility, thus requiring the addition of propylene glycol to act as a cosolvent to improve these characteristics. After the reconstitution of melphalan with propylene glycol–containing solution, impurities can develop within 30 minutes, and if further dilution occurs, the potency of melphalan diminishes. Propylene glycol is associated with a spectrum of toxicities that can be dose limiting. Evomela is a propylene glycol-free melphalan (PGF-Mel) that at a high dose of 200 mg/2 (100 mg/m2/d for 2 days) is approved for conditioning before AHCT in MM patients. Once reconstituted by directly dissolving in saline solution, PGF-Mel solution can be stored in the vial for up to 1 hour at room temperature or for up to 24 hours at refrigerated temperature (2° to 8°C) with no significant degradation. The demonstrated stability, up to 24 hours at room temperature, results in reduced handling requirements and increased convenience and flexibility of administration. Since its approval, Evomela has been the subject of several retrospective and investigator-initiated studies. This review summarizes the prospective and real-world evidence on practical aspects of PGF-Mel and critically appraises the available data and its clinical implications.